Design Development of Batik Mangrove Wonorejo Surabaya - Muchlisiniyati Safeyah; Afif Fajar Zakariya (Nusantara Science and Technology Proceedings, 2023)
Wonorejo mangrove batik, Rungkut Surabaya has its uniqueness. Mangrove batik motifs contain philosophical meanings about environmental sustainability and the relationship between humans and nature. The design motifs come from the mangrove forest ecosystem, such as fruit, leaves, and flowers. Also from several marine ecosystems, such as mackerel fish, coral reefs, jellyfish, and others. The Wonorejo mangrove batik design is important to develop as an effort to strengthen local cultural identity and promote Wonorejo's natural heritage. Using a qualitative approach by exploring the creative process, cultural values, and social and economic impacts of the design development. The Wonorejo mangrove batik design was developed by combining batik art with the natural environment of the Wonorejo mangrove forest. The new elements presented in the batik design are a combination of traditional and modern art, elements of the mangrove forest ecosystem in the form of mangrove plant stems, and coastal atmosphere in the form of sea and sand.